Association Between Eight Weeks Of Isometric Handgrip Training And Angiotensin Converting Enzyme Insertion/deletion Gene Polymorphism In Hypertensive Individuals. - Yusof, Wan Mohammad Nazrin Wan (2024)
A prevalent global health concern is hypertension, affecting over 1 billion people worldwide. Physical exercise plays a crucial role in the lifestyle management of individuals with high blood pressure. This investigation seeks to link ACE I/D gene polymorphism with the effects of eight weeks isometric handgrip (IHG) training and detraining regimen on cardiovascular and muscular function in unmedicated hypertensive population in Malaysia. To assess the cardiovascular and muscular impacts of an eight-week IHG and detraining program across different ACE I/D genotype groups, this study involved fifty-eight unmedicated individuals with hypertension. They were randomly assigned to two groups, namely the training and control groups. The training group comprised 29 participants (mean age: 40.45 ± 9.22), consisting of 22 males and seven females. Simultaneously, the control group included 29 participants (mean age: 37.41 ± 9.03), with 15 males and 14 females. Participants in the IHG group received IHG training three times per week for eight weeks, followed by another eight weeks of detraining in which they did not receive IHG training or any organized exercise. For eight weeks, those in the control group (CON) did not participate in any exercise regimen. Based on the findings of the present study, an eight-week IHG training program resulted in a reduction of the cardiovascular parameter, as indicated by a decrease in systolic blood pressure (SBP), while maintaining consistent levels of muscle variables.